Consensus on Prostate Cancer Treatment of Localized Disease With Very Low, Low, and Intermediate Risk: A Report From the First Prostate Cancer Consensus Conference for Developing Countries (PCCCDC). (2021) - Luz, Murilo de Almeida; Guimarães, Gustavo Cardoso; Nardi, Aguinaldo César; Pompeo, Alexandre Saad Feres Lima; Sarkis, Álvaro Sadek; Nowier, Amr; Lima Pompeo, Antônio Carlos; Nardozza, Archimedes; Adamy, Ari; Carneiro, Arie; Salvajoli, Bernardo Peres; Benigno, Bruno Santos; et al.
Abstract : PURPOSE: A group of international urology and medical oncology experts developed and completed a survey on prostate cancer (PCa) in developing countries. The results are reviewed and summarized, and recommendations on consensus statements for very low-, low-, and intermediate-risk PCa focused on developing countries were developed. METHODS: A panel of experts developed more than 300 survey questions of which 66 questions concern the principal areas of interest of this paper: very low, low, and intermediate risk of PCa in developing countries. A larger panel of 99 international multidisciplinary cancer experts voted on these questions to create the recommendations for treatment and follow-up for very low-, low-, and intermediate-risk PCa in areas of limited resources discussed in this manuscript. RESULTS: The panel voted publicly but anonymously on the predefined questions. Each question was deemed consensus if 75% or more of the full panel had selected a particular answer. These answers are based on panelist opinion not a literature review or meta-analysis. For questions that refer to an area of limited resources, the recommendations consider cost-effectiveness and the possible therapies with easier and greater access. Each question had five to seven relevant answers including two nonanswers. The results were tabulated in real time. CONCLUSION: The voting results and recommendations presented in this document can be used by physicians to support management for very low, low, and intermediate risk of PCa in areas of limited resources. Individual clinical decision making should be supported by available data; however, as guidelines for treatment for very low, low, and intermediate risk of PCa in developing countries have not been developed, this document will serve as a point of reference when confronted with this disease.